Cytotoxic triterpenoid glycosides (saikosaponins) from the roots of Bupleurum chinense. Issue 18 (15th September 2015) - Li, Dan-Qi; Wu, Jie; Liu, Li-Yin; Wu, Ying-Ying; Li, Ling-Zhi; Huang, Xiao-Xiao; Liu, Qing-Bo; Yang, Jing-Yu; Song, Shao-Jiang; Wu, Chun-Fu
Graphical abstract: Abstract: As a part of our ongoing studies on cytotoxic triterpenoid saponins from herbal medicines, phytochemical investigation of the roots of Bupleurum chinense DC. afforded four new saikosaponins (1 –4 ), along with 16 known ones (5 –20 ). Their structures were established by direct interpretation of their spectral data, mainly HR-ESI-MS, 1D NMR and 2D NMR, and by comparison with literature data. Among them, compound20 was isolated from the natural product for the first time. The cytotoxicities of all compounds against five selected human cancer cell lines (A549, HepG2, Hep3B, Bcap-37 and MCF-7) were assayed. In general, a number of the isolated compounds exhibited potent cytotoxic activities against the five selected human cancer cell lines. In particular, compounds3, 8 –9, 11 –13, 16 and20 showed more potent cytotoxic activities against the HepG2 and A549 cell lines than the positive control 5-fluorouracil. Based on the primary screening results, the preliminary structure–activity relationship (SAR) studies were also discussed. The SAR results suggest that the 13, 28-epoxy bridge, the orientation of the hydroxyl group and the type of the sugar units are important requirements for cytotoxicity and selectivity.